2022
DOI: 10.1515/jmbm-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of welding consumables on shielded metal arc welded ultra high hard armour steel joints

Abstract: Materials with high hardness are usually preferred in armour applications and are difficult to weld due to high Carbon Equivalent (C.E). In this investigation, an attempt was made to weld Ultra-high Hard Armour (UHA) steel (having C.E of 0.91) by Shielded Metal Arc Welding (SMAW) process using three electrodes (i) austenitic stainless steel (ASS- E307-16), (ii) super duplex stainless steel (SDSS-E2594-16) (iii) low hydrogen ferritic (LHF-E12018M-low-alloy steel electrode). The mechanical properties (tensile, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Additionally, Kumar et al 12 reported similar results utilising welding on Armour steel. The addition of chromium stabilises the ferrite phase and effectively slows the onset of the transition temperature.…”
Section: Sem/eds Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…Additionally, Kumar et al 12 reported similar results utilising welding on Armour steel. The addition of chromium stabilises the ferrite phase and effectively slows the onset of the transition temperature.…”
Section: Sem/eds Analysismentioning
confidence: 72%
“…The occurrence of fracture growth may be influenced by the GBP (white phase). 12 The particular weld heat cycle used in the joint manufacturing process affects the production of this phase. The current investigation used austenitic filler wire to compare the GTAW, GMAW, SMAW, and FCAW techniques on an 18 mm thick plate made of armour steel.…”
Section: Introductionmentioning
confidence: 99%